2022
DOI: 10.1038/s41598-022-22244-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human milk oligosaccharides in early lactation and relation with growth and appetitive traits of Filipino breastfed infants

Abstract: Human milk oligosaccharides play a key role in the maturation of the infant gut microbiome and immune system and are hypothesized to affect growth. This study examined the temporal changes of 24 HMOs and their associations to infant growth and appetitive traits in an exploratory, prospective, observational, study of 41 Filipino mother-infant dyads. Exclusively breastfed, healthy, term infants were enrolled at 21–26 days of age (≈ 0.75 mo) and followed for 6 months. Infant growth measures and appetitive traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The second metric, height gain, was reported in 12/19 studies as either weight for length z score, length for age z score, or height for age z score. The following HMOs had a positive correlation with height gain: 2’FL [30,31,47,48], 3FL [43], 3’SL [39,43], LNnT [39], LST-a [49,51], DFLNH [41,43,51], and DFLNT [43] while a negative correlation was linked with: 3FL [52], 3’SL [46], 6’SL [49], LNnT [30,39,43,46], LNT [31,39], LNFP I [39,47], LNFP II [32], LST b [30,31,49], and FLNH [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second metric, height gain, was reported in 12/19 studies as either weight for length z score, length for age z score, or height for age z score. The following HMOs had a positive correlation with height gain: 2’FL [30,31,47,48], 3FL [43], 3’SL [39,43], LNnT [39], LST-a [49,51], DFLNH [41,43,51], and DFLNT [43] while a negative correlation was linked with: 3FL [52], 3’SL [46], 6’SL [49], LNnT [30,39,43,46], LNT [31,39], LNFP I [39,47], LNFP II [32], LST b [30,31,49], and FLNH [39].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the sociodemographic and HMO data from the 27 studies that were included in this review. The selected studies were conducted in 21 countries: Australia [31,43]; Bangladesh [53]; Brazil [36,50]; China [32,41]; Denmark [54]; Finland [30]; France [48]; Gambia [18]; Germany [39]; Kenya [42]; Malawi [47,51]; Netherlands [44]; Philippines [52]; Singapore [33]; Spain [40]; Sweden [49]; and USA [17,34,35,37,38,45]. In addition, there was one European Union study involving milk samples collected from France, Italy, Norway, Portugal, Romania, Spain and Sweden [46].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Multiple studies, although inconsistent, have identified various associations between individual HMOs and/or HMO diversity and infant growth [ 77 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Most of the previous studies have measured HMOs using high-performance liquid chromatography–mass spectrometry (HPLC-MS) in conjunction with fluorescent derivatisation [ 59 , 77 , 78 , 84 , 85 , 86 , 87 , 88 , 90 , 91 ], and two have used nano-LC-chip/time-of-flight (TOF)-MS [ 83 , 89 ].…”
Section: Human Milk Oligosaccharides (Hmos)mentioning
confidence: 99%
“…Multiple studies, although inconsistent, have identified various associations between individual HMOs and/or HMO diversity and infant growth [ 77 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Most of the previous studies have measured HMOs using high-performance liquid chromatography–mass spectrometry (HPLC-MS) in conjunction with fluorescent derivatisation [ 59 , 77 , 78 , 84 , 85 , 86 , 87 , 88 , 90 , 91 ], and two have used nano-LC-chip/time-of-flight (TOF)-MS [ 83 , 89 ]. However, differences in study populations and design, including sample time point(s) and reporting styles for infant growth data, make it difficult to identify any consensus between studies, with contradictory associations reported for some HMOs ( Table 1 ).…”
Section: Human Milk Oligosaccharides (Hmos)mentioning
confidence: 99%
“…Human milk contains infant's nutrients and bioactive components that support appropriate growth, digestibility, and tolerance [7,8] . Breastfeeding has a distinctive protective role since breastfed infants have a lower incidence of diarrhea, allergies, and inflammatory diseases, contributing additional benefits to immune system development [9][10][11] . Breast milk contains high concentrations of free human milk oligosaccharides (HMOs).…”
Section: Introductionmentioning
confidence: 99%